Trends in Early Hospital Readmission After Kidney Transplantation, 2002 to 2014: A Population-Based Multicenter Cohort Study. Issue 4 (April 2018) - Naylor, Kyla L.; Knoll, Gregory A.; Allen, Britney; Li, Alvin H.; Garg, Amit X.; Lam, Ngan N.; McCallum, Megan K.; Kim, S. Joseph
Abstract : Background: Early hospital readmission (EHR) is associated with morbidity, mortality, and significant healthcare costs. However, trends over time in EHR events in kidney transplant recipients have not been examined. We conducted a population-based cohort study using linked healthcare databases from Ontario, Canada, to determine whether the EHR incidence has changed from 2002 to 2014 in kidney transplant recipients. Methods: We defined EHR as an unplanned admission for any reason to an acute care hospital within 30 days of being discharged from the hospital for transplantation; admissions for elective procedures were excluded. Results: We included 5437 kidney transplant recipients. More recently transplanted recipients (2011 to 2014 vs 2002 to 2004) were older and more likely to have coronary artery disease. A total of 1128 (20.7%) kidney transplant recipients experienced an EHR. There was no trend in EHR across eras with a 30-day cumulative incidence of 23.0%, 21.4%, 18.4%, and 21.0% ( P for trend =0.197) for the years 2002 to 2004, 2005 to 2007, 2008 to 2010, and 2011 to 2014, respectively. In the multivariable Cox proportional hazards model, we found no association between era of transplant and EHR. When examining variation in EHR across the 6 adult transplant centers, we found the 30-day cumulative incidence varied significantly from 15.5% to 27.1% ( P < 0.001). Conclusions: One in 5 kidney transplant recipients will experience an EHR; however, an increase in EHR over time has not been observed despite increasing recipient age and comorbidities. Abstract : In Ontario, Canada, the authors show that early hospital readmisssion (within 30 days postdischarge) in kidney transplant recipients has not changed over time between 2002 to 2014, despite a population of recipients becoming older with more prevalent coronary disease. Supplemental digital content is available in the text.